Who were the Vikings? - Chisholm, Jane.; Reid, Struan; Cuzik, David (London : Usborne ; Tulsa, Okla. : EDC Pub., 2002)
Describes the everyday lives of the Vikings, covering their appearance, families, homes, food, medicine, recreation, shopping, transportation, armies, and religion, and providing related Web site addresses.
"First published in 1995 by Usborne Publishing Ltd"--Colophon.
"With Internet links"--Cover.
Includes index.
4.7
K-3
Keywords: Vikings -- Juvenile literature; Vikings -- Social life and customs -- Juvenile literature; Civilization, Viking -- Juvenile literature; Vikings; Vikings